Can Hemogram Parameters Predict a Positive PCR Result in COVID-19? (Bangladesh Journal of Medical Science, 2022)
Objective: Quick diagnosis of COVID-19 has been an important factor to manage the ongoing pandemic at hospitals and other health facilities. We aimed to investigate the effects of PCR test on hemogram parameters in COVID-19 patients.Materials and Methods: We collected hemogram data of 120 nasopharyngeal and oropharyngeal combo swab PCR positive and 119 PCR negative patients admitted to our hospital’s COVID-19 clinics with COVID-19 symptoms between 1 April 2020 and 24 June2020.Results: Age, MPV and NLR were found to be higher; hemoglobin, neutrophil, lymphocytes, basophil, platelet, PCT, WBC levels were lower in PCR positive cases. The highest sensitivity, 75 % is found on WBC count with cut off 7.15.Conclusion:Lower leukocyte count than 7.15, lower neutrophil count than 4.91, greater NLR than 2.95, lower platelet than 221.5 may give an idea about the diagnosis of SARS-CoV-2 infection.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 391-397